Abdurrahman Al- Nasir : Studi atas Peranannya dalam Pengembangan Ilmu Pengetahuan di Andalusia - Samsir Samsir (Dinamika Ilmu, 2009)
Abdurrahman al-Nasir was the leader of Bani umayyah in Andalusia that famous and be a good model for every people. In his government period, Bany Umayyah could achieve the glory especially in knowledge field. In advancing the society’s need of knowledge, Abdurrahahman al-Nasir built Cordova University and library to facilitate the education system. Furthermore, education world in Abdurrahman al-Nasir government period becomes the priority and made Cordova as the center of intellectual activities, it was the same that happened in Toledo and Suville. The education center connected the education dualism of Religious knowledge and general knowledge such as Astronomy, Geometry, Health, Law, History, Language, Geography, and Science. Soon there were born Muslim scientists from any kinds of knowledge fields. With the persistence of Abdurrahman al-Nasir, he created the composure and also the prosperous Andalusia especially Cordova. With the result that Islamic government in the West painted the brilliant history and could compete with Islamic civilization in the East.